ADAPTATION AND TRANSFORMATION OF MARKETING PERSONNEL ROLES UNDER THE INFLUENCE OF DIGITALIZATION (Regional aspects of productive forces development of Ukraine, 2024)
Introduction. The relevance of the research topic is defined by the global transformations in the marketing sphere that are happening under the influence of the rapid development and implementation ofdigitalization technologies. This fundamentally changes the conditions, content and nature of marketing specialists' work, determining completely new analytical and communication challenges. However, currently there is a lack of comprehensive developments regarding the specifics of marketers' adaptation to the updated realities of the digital age and the features of the transformation of their professional roles. So the chosen issue for analysis is extremely relevant.Goal. To identify key challenges facing marketers in the context of digitalization of business based on the systematization of scientific views and the author's interpretation; to outline necessary adaptationmeasures; characterize the transformation of the professional roles of a senior marketer as a specialist responsible for developing a marketing strategy.Methods. To achieve this goal, a set of general scientific methods of cognition was used, which ensured the consistency and logical consistency of the conclusions.Results. It is proved that in an era of pervasive digitalization, the role of a marketer is transformed towards strengthening his analytical and prognostic functions. It is proved that marketers face fundamental challenges associated with a sharp increase in data volumes, the need to master new  methods of processing them, the formation of new communication practices with consumers and staff.It is established that against the background of digitalization the professional roles of a senior marketer are being transformed, who takes on new functions as an analyzer of creative ideas, an assessorof business prospects, a guarantor of the company's image, a consultant and coach on effective communications, which requires him to master a number of soft and hard skills, as well as adaptation tothe modern digital environment.Conclusions. The results indicate the expediency of developing practical recommendations for the formation of adaptive marketing models against the background of digital transformations, which could become an area for further research.